Structural and hydrogen storage characterization of nanocrystalline magnesium synthesized by ECAP and catalyzed by different nanotube additives - Révész Ádám (De Gruyter, 2021)
Ball-milled nanocrystalline Mg powders catalyzed by TiO2 powder, titanate nanotubes and carbon nanotubes were subjected to intense plastic deformation by equal-channel angular pressing. Microstructural characteristics of these nanocomposites have been investigated by X-ray diffraction. Microstructural parameters, such as the average crystallite size, the average dislocation density and the average dislocation distance have been determined by the modified Williamson–Hall analysis. Complementary hydrogen desorption and absorption experiments were carried out in a Sieverts’ type apparatus. It was found that the Mg-based composite catalyzed by titanate nanotubes exhibits the best overall H-storage performance, reaching 7.1 wt% capacity. The hydrogenation kinetic curves can be fitted by the contracting volume function for all the investigated materials. From the fitted parameters, it is confirmed that the titanate nanotube additive results in far the best kinetic behavior, including the highest hydride front velocity.